Development of NBM Home Tuition Management System - Mohammad Mustafa, Nur Hamizah; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2023)
NBM Home Tuition is an education centre that manages its operations manually because it lacks a proper learning management system (LMS). LMS is a system that assists in the administration of educational institute. NBM Home Tuition confronts a few issues due to the lack of a system, such as pupils being uninformed of the upcoming works. The main research objectives are to design NBM Home Tuition Management System using an object-oriented approach, to develop the system using a web-based approach and to test the developed system using functional testing and unit testing. The project target users are teachers, students, and admins. The modules of the proposed system are the login module, registration module, assigned task module, task management module, payment and reporting module, and announcement module. The project used prototyping model to develop the system. At the end of this project, a tuition management system is expected to be developed.